Having a Parent with Early-Onset Dementia: A Qualitative Study of Young Adult Children - Hanne Groennestad; Wenche Malmedal (Hindawi Limited, 2022)
Background. Children of a parent with early-onset dementia (EOD) are confronted with losing a parent to a progressive neurodegenerative illness, usually perceived as an older adult illness, which may have a great impact on their lives at a time that is usually preserved for self-development. Objective. The objective of this study is to explore the experiences and perceptions of young adult children of a parent with EOD, with specific focus on personal lives and family and social relationships in a Norwegian context. Methods. Semistructured interviews with 10 young adult children between the ages of 19 and 30 years of a parent with EOD were analysed using a thematic analysis. Results. The analysis identified six main themes. "Upon discovering dementia, Keeping the family together, Others do not understand, A sense of relief, A need for support" and Apprehension for the future. The participants expressed an overarching feeling of living parallel lives, summarised by the phrase "We are not in the same boat." Furthermore, the themes demonstrated that the participants experienced difficulties with managing new responsibilities, at the same time, as preserving their own lives. They also shared concerns about the future and often experienced a lack of understanding and support from others. Finally, the need for targeted support throughout the illness was a central theme, whereby many felt more comfortable talking with someone with similar experiences or knowledge of their situation. Conclusion. The findings in this study strengthen the notion that the children of persons with EOD experience a challenging life situation, underlining the need for a person- and family-oriented approach.